﻿Analysis of fall risk increasing drugs on Morse Fall Scale in geriatric patients (a study at geriatric outpatient clinic Airlangga University Teaching Hospital) - Yulistiani Yulistiani; Febriansyah Nur Utomo; Cahyo Wibisono Nugroho; Yasmin N. Izzati (Pensoft Publishers, 2023)
Falls are the geriatric syndromes that become one of the main causes of injury, even death in the elderly. It is known that one of the risk factors for falling is the use of certain drugs that have the effect of orthostatic hypotension, sedation, balance disruptions, and other side effects. This study aims to examine the risk of falling based on Morse scale of geriatric patient that use fall-risk drug. Retrospective data were taken from e-prescriptions for geriatric patients and interviews with the patients to determine the risk of falling based on the Morse scale. The results showed that 115 patients who used the fall-risk drug had an average risk of falling from mild to moderate. The high fall-risk drug used by most patients was gabapentin (43%), the moderate fall-risk drug was candesartan (60%), and the low fall-risk drug was furosemide (9%). Patients with the total of 71% received a combination of two to four fall-risk drugs. Total MFRS of ≥6 was 53% patients, meaning that the patients' using of drugs needed to be evaluated. From the results of statistical analysis, it was found that the number of fall risk drugs received by patients was not associated to the risk of falling in geriatric patients, while increasing the dose of high fall-risk drugs such as gabapentin, increased the fall risk level in geriatric patients. From the result of this study, it is known that fall-risk drugs are widely used by patients, hence it is necessary to increase the awareness of falling in geriatric patients.